Effects of Triple Super Phosphate and inoculant on yield of soybean seed in Northern Region of Ghana (Ghana Journal of Science, Technology and Development, 2021)
The research was conducted to establish the effects of triple super phosphate and rhizobia inoculant on yield of soybean (Glycine Max (L)) seed quality in the Northern region of Ghana. Multi-locational trials were adopted and three different locations were used.  Soybean foundation seeds obtained from Savannah Agriculture Research Institute were subjected to three different treatments on the field. These treatments were TSP + Inoculant, TSP only, Inoculant only and a control plot as a check. Randomize complete block design was used to allocate the treatments to the various plots. Data collected from the field included: number of days from seeding to germination, flowering and pod formation; nodule formation; plant height, number of pods per plant per treatment (Pod load), number of days to maturity, seed weight at harvest per plant per treatment (1000 seed weight) and finally, the yield was determined after harvest. Results revealed that the treatments (TSP + Inoculant, TSP only and Inoculant only) generally enhanced growth, development and yield of soybean seed as compared to the control plots in almost all the locations. The application of Rhizobia inoculant contributed significantly to the development of the soybean plant. It aided the fixation of atmospheric nitrogen into the soil which improved its fertility that led to the significant increase in the number of nodules that were formed by the plant.  The pod load was very high for all the treated plots. They were fully filled with seeds which were evidence in the yield obtained from the trials.  TSP in combination with inoculants gave a very good yield of 2.66 Mt/ha and was significantly higher than all the other treatments. This result is a clear indication of how phosphorus fertilizer and inoculant positively affected the yield. Seed producers should be encouraged, in addition to good agronomic practices, to apply the recommended dosage of inoculant and TSP to their seeds and soybean fields respectively. This would lead to early maturity and high yields.Keywords: Soybean seed, Northern region of Ghana, Phosphorus, Inoculant, Yield